Leadership in Action : Leadership in an Instant - Nilsen, Gina Hernez-Broome. Dianne (Center for Creative Leadership, 1999)
There are instances when a single act establishes someone as an effective or ineffective leader, when the leader does or says something that makes a lasting impression on people and deeply affects those involved.